"Warming Someone's Soul with Your Own Hands": Ruvim Fraerman's Children's Prose and the Legacy of Russian Modernism. (2nd October 2019) - Maiofis, Maria
ABSTRACT: In her article, Maria Maiofis argues that Ruvim Fraerman's 1939 work Wild Dog Dingo, Or a Story of First Love [Dikaia sobaka Dingo, ili Povest' o pervoi liubvi] is not primarily intended as a story of adolescent love but rather of the vicissitudes of a teenaged girl's relationship with her divorced parents. Fraerman's treatment of adolescent psychology and the difficult path into adulthood reflects the legacy of Russian modernist prose and aspects of psychoanalytic theory, which he may have become familiar with firsthand in the 1910s or 1920s or indirectly through Russian modernist prose.